Selective and ratiometric fluorescence sensing of bisphenol A in canned food based on portable fluorescent test strips - Liu, Xiqing; Wang, Tao; Wang, Yongqing (Analytica chimica acta, 2023)
In this study, a conversion method and molecular imprinting technology were used to design molecularly imprinted polymers (MIP)-based ratiometric fluorescence test papers. The ZnO quantum dots (ZnO QDs) acted as the background quantum dots and ZIF-8 raw material. Carbon dots (CDs) were used as the identification signals. The imprinting layer achieved a selective function. Therefore, a ZnO@ZIF-8/CDs@MIPs sensor was designed for the detection of Bisphenol A (BPA). The sensor exhibited a fast response time for BPA detection. In addition, the sensor demonstrated that effective detection of BPA can still be achieved in complex environments. The detection limit of this sensor was 0.778 nM with a linear range of 0–60 nM. The corresponding test solutions exhibited clear changes from blue to yellow. The selectivity experiments results demonstrated that ZnO@ZIF-8/CDs@MIPs only exhibit excellent selective recognition effect for BPA. ZnO@ZIF-8/CDs@MIPs-2 was used for the detection of BPA in canned food and compared with the results of HPLC detection of BPA. The two spiked recovery ranges were 96.58–102.04% and 97.43–103.82%, respectively. In addition, the prepared ZnO@ZIF-8/CDs@MIPs-2 test paper visually recognized BPA under ultraviolet light. This study provides guidelines for the design and application of fluorescent test papers for quick detection in practical applications. A ZnO@ZIF-8/CDs@MIPs fluorescence sensor was constructed for selective and sensitive detecting bisphenol A (BPA) with naked-eye observation. [Display omitted] •ZnO@ZIF-8 core-shell nanodots were prepared by self-template method.•A novel ZnO@ZIF-8/CDs@MIPs-2 with visualization and selectivity was synthesized by precipitation polymerization.•Portable fluorescent test strips were designed for timely detection.•The actual sample detection results of the fluorescence sensor were consistent with HPLC method.